MosqTent: An individual portable protective double-chamber mosquito trap for anthropophilic mosquitoes. - José Bento Pereira Lima; Allan Kardec Ribeiro Galardo; Leonardo Soares Bastos; Arthur Weiss da Silva Lima; Maria Goreti Rosa-Freitas (Public Library of Science (PLoS), 2017)
Here, we describe the development of the MosqTent, an innovative double-chamber mosquito trap in which a human being attracts mosquitoes while is protected from being bitten within the inner chamber of the trap, while mosquitoes are lured to enter an outer chamber where they are trapped. The MosqTent previously collected an average of 3,000 anophelines/man-hour compared to 240 anophelines/man-hour for the human landing catch (HLC), thereby providing high numbers of human host-seeking mosquitoes while protecting the collector from mosquito bites. The MosqTent performed well by collecting a high number of specimens of Anopheles marajoara, a local vector and anthropophilic mosquito species present in high density, but not so well in collecting An. darlingi, an anthropophilic mosquito species considered the main vector in Brazil but is present in low-density conditions in the area. The HLC showed a higher efficiency in collecting An. darlingi in these low-density conditions. The MosqTent is light (<1 kg), portable (comes as a bag with two handles), flexible (can be used with other attractants), adaptable (can be deployed in a variety of environmental settings and weather conditions), and it can be used in the intra-, peri-, and in the extradomicile. Also, the MosqTent collected similar portions of parous females and anthropophilic mosquito species and collects specimens suitable for downstream analysis. Further developments may include testing for other fabric colors, different mesh sizes and dimensions for other hematophagous insects and conditions, additional chemical mosquito attractants, and even the replacement of the human attractant in favor of other attractants. MosqTent modifications that would allow the trap to be applied as a vector control tool with killing action could also be explored.